Finite element modelling of 10-year-old child pelvis and lower extremities with growth plates for pedestrian protection. (2015) - Shen, Ming; Zhu, Feng; Mao, Haojie; Fan, Haonan; Mone, Nikhil; Sanghavi, Vikas; Kalra, Anil; Jin, Xin; Chou, Clifford C.; Yang, King H.
For improved protection for pedestrians in the 10 years (YO) old age group, it is imperative to investigate the injury mechanisms using paediatric finite element (FE) model. A 10 YO child FE pelvis and lower extremities (PLEX) model was developed in this study. The model was validated by comparing simulated results against available paediatric experimental data and scaled adult test results. Growth plates were then embedded into this baseline model at the lower extremities. The anatomical features were kept and the mechanical properties were properly estimated based on literature findings. Subsequently, the effect of the growth plates at knee joint regions was studied in a car-to-pedestrian impact scenario. Results showed that the presence and early fracture of growth plates at knee region could alter the injury pattern at the lower extremities. Failure criterion of tension or shearing assumed in this model could also greatly influence the fracture progress.